1997
DOI: 10.1073/pnas.94.21.11686
|View full text |Cite
|
Sign up to set email alerts
|

Peptide analogue studies of the hypothalamic neuropeptide Y receptor mediating pituitary adrenocorticotrophic hormone release

Abstract: Hypothalamic neuropeptide Y (NPY) is thought to be important in the regulation of feeding and also in the release of Adrenocorticotrophic hormone (ACTH). Intracerebroventricular administration of NPY to male rats significantly increased plasma ACTH 10 min after injection and stimulated 2-h food intake. Neuropeptide Y (NPY) is a 36-amino acid peptide of the pancreatic polypeptide family, with homology to pancreatic polypeptide (PP, Ϸ50%) and peptide YY (PYY, Ϸ70%) (1). NPY is one of the most abundant neuropepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…It has been shown that only intact NPY can stimulate ACTH and cortisol release in dogs, whereas its C-terminal fragment, NPY (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), and the NPY analog, NPY (1-36)-OH, are ineffective (12). In contrast, Small et al (18), using different NPY analogs, have obtained results suggesting that the rat hypothalamic NPY receptor, which increased plasma ACTH concentrations, has a fragment activation profile unlike those of Y1-Y4 and Y6 receptors, and appears distinct from the NPY receptor controlling food intake. They also suggest that the activity of this receptor seems to be similar to that of the Y5 receptor.…”
Section: Role Of Npy In Regulation Of the Hpa Axis In The Hypothalamusmentioning
confidence: 98%
“…It has been shown that only intact NPY can stimulate ACTH and cortisol release in dogs, whereas its C-terminal fragment, NPY (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), and the NPY analog, NPY (1-36)-OH, are ineffective (12). In contrast, Small et al (18), using different NPY analogs, have obtained results suggesting that the rat hypothalamic NPY receptor, which increased plasma ACTH concentrations, has a fragment activation profile unlike those of Y1-Y4 and Y6 receptors, and appears distinct from the NPY receptor controlling food intake. They also suggest that the activity of this receptor seems to be similar to that of the Y5 receptor.…”
Section: Role Of Npy In Regulation Of the Hpa Axis In The Hypothalamusmentioning
confidence: 98%
“…Intracerebroventricular (ICV) administration of NPY stimulates food intake (Clark et al 1985;Levine and Morley 1984;Stanley and Leibowitz 1984), modulates cognition (Flood et al 1987;Redrobe et al 1999), inhibits neuronal excitability (Colmers and Bleakman 1994) and has anticonvulsant effects (Vezzani et al 1999). NPY modulates the secretion of various hypothalamic neuropeptides, stimulates the corticotrophic axis (Krysiak et al 1999;Small et al 1997) and has potent inhibitory effects on gonadotrophic and somatotrophic axes (Catzeflis et al 1993). In addition, NPY is thought to play a role in the pathophysiology of certain mood disorders and in the mechanism of action of antidepressant drugs (Heilig et al 1988;Caberlotto et al 1998 (Michel et al 1998).…”
Section: The Present Study Was Undertaken To Investigate the Possiblementioning
confidence: 99%
“…After this period, rats were given a further week of daily handling to habituate them to all experimental procedures and minimize stress. A positive dipsogenic response to ICV injection of angiotensin II (ANG II; 150 ng/rat), as previously described (16,40,41), verified cannula placement. If an animal ate <10 g of food in a 24-h period or lost >10 g body wt over a 48-h period, it was considered unwell and excluded from the study.…”
Section: Methodsmentioning
confidence: 99%